2022-RA-1170-ESGO Can serum level of WT1 gene replace gene expression in the diagnosis of ovarian cancer?. (20th October 2022) - Ranjan, Amar; Dubey, Harshita; Tanwar, Pranay
Abstract : Introduction/Background: WT1 gene and its encoded protein are highly expressed in hematological malignancies and solid tumors such as cancer of breast, lung, pancreas, ovary and prostate (1). WT1-expression is examined by IHC or qPCR, while WT1- ELISA kit is also available. We compared serum level of WT1 (sWT1) with its expression in ovarian cancer (OC) patients. Methodology: We studied 30 OC-cases 11 benign ovarian cysts (control). Their sWT1 was measured from samples collected prior to surgery or chemotherapy. ROC curve analysis was done to have a cut-off to differentiate benign from malignant lesions. It was 3.35ng/mL at 64% sensitivity and 63% specificity with AUC 0.61. Intra-operatively, tumor tissues of 22 OC-cases were collected and examined for RNA expression, which are being compared with sWT1 in this study. Results: In the two techniques, out of 22 cases, high & low values were seen in 15(68.1%) & 7 (31.8%) cases respectively. But the cases were different ( table 1 ). qPCR: High wt1-expression was seen in 15, out of which 4 (26.6%) showed low serum level, whereas 11 (73.3%) showed high sWT1. Out of 7 low expression cases, low and high serum levels were seen in 3 & 4 cases ( table 1 ). sWT1: It was high in 15, out of which 11 (73.3%) showed high expression & 4 (26.6%) showed low expression. Out of 7 low sWT1, 4 (57.1%) showed high expression and 3 (42.8%) showed low expressions ( table 1 ). Conclusion: We couldn't find any study, in which WT1 gene expression was compared with that of serum level. This is first pilot study, which shows that there is no correlation between gene expressions with that of their serum levels, although number cases may be required for conclusive result.